CLOUD-BASED PRINT MANAGEMENT SYSTEMS - Dhabliya, Dharmesh; Dev, Sudhanshu; Canessane, R Aroul; Patil, Shashikant; Sharma, Vivek Kumar; Kaur, Sumeet; Shukla, Bhupesh Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Cloud-Based Print Management Systems represent a paradigm shift of the old style of on-shelf print infrastructures to an innovative, scalable, secure, and cost-effective print systems hosted by the cloud. These systems use cloud computing to print jobs, user authentication, and device communication without any complications in various platforms and network environments. The architecture is usually made up of the following core components which are: print servers, connectors, clients, and end-user devices and they are built using standardized workflows and APIs to guarantee that they will be interoperable with enterprise systems and networks. Some of the main features are secure print release system, highly developed authentication, smart routing of print jobs, mobile device-ability, which guarantees flexibility and access by distributed workforces. Centralized control and compliance monitoring help organizations to save on capital expenditure, streamline maintenance, increase scalability levels, and ensure better security. It is still facing challenges with data privacy, network latency and interoperability with legacy systems though, and it requires a strong encryption solution, redundancy plans and deployment choices on a hybrid basis. The comparative analysis of the top known solutions, namely, Microsoft Universal Print, Papercut, and PrinterLogic, reveals three different degrees of scalability, integration with the main enterprise, and compliance preparedness after Google Cloud Print was discontinued.